ANALISIS PENGARUH KEBIJAKAN PEMERINTAH SISTEM LOGISTIC DAN KUALITAS PRODUK TERHADAP KINERJA EKSPOR DI PELABUHAN TANJUNG EMAS SEMARANG - Agus Santosa (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2018)
There are many factors affecting export performances, such as: government policy, logistics system, product policy all of which greatly affect export performances. Globalization could also cause relations between countries closer due to the interaction in political, defense, and economic cooperation. One form of cooperation is the ASEAN economic communities; this will make competition between ASEAN countries more stringent. That is why Indonesia needs to prepare in all respects including aspects of export-import performances.This research was analyzed using three variables they are government policy, logistic system and product quality as independent variable influencing dependent variable that is export performance. In this research the object taken is manufacturing companies that actively carry out export activities at Tanjung Emas Port of Semarang. Data sources include primary and secondary data. The sample in this study is 124 manufacturing companies that actively carry out export activities at the Tanjung Emas Port of Semarang. Data analysis technique is multiple linear regression technique. The result of multiple linear regression equation showed that there were a positive influence partially between government policy toward export performance meaning that independent variable influences simultaneously to dependent variable, government policy variable, logistic system and product quality influences by 44,2% toward export performance and 55,8% influenced by undetectable research variables.Keywords : Export Performance, Government Policy, Logistics System, Product QualityBanyak faktor yang mempengaruhi kinerja ekspor, seperti : kebijakan pemerintah, sistem logistik, kebijakan produk yang kesemuanya itu sangat mempengaruhi kinerja ekspor. Pada penelitian ini akan dinanalisis tiga variabel penelitian yaitu kebijjakan pemerintah, sistem logistik dan kualitas produk sebagai independen variabel yang mempengaruhi dependen variabel yaitu kinerja ekspor. Pada penelitian ini obyek independen adalah perusahan Manufakturing yang aktif melaksanakan kegiatan ekspor di Pelabuhan Tanjung Emas Semarang. Sumber data primer dan. Sampel pada penelitian ini adalah 124 responden yang merupakan perusahan Manufakturing yang aktif melaksanakan kegiatan ekspor di Pelabuhan Tanjung Emas Semarang. Teknik analisis datanya adalah teknik regresi linier berganda. Hasil persamaan regresi linier berganda menunjukkan bahwa ada pengaruh yang positif antara variabel independen terhadap variabel dependen, yaitu variabel kebijakan pemerintah, sistem logistik dan kualitas produk berpengaruh 44,2% terhadap kinerja ekspor dan 55,8% secara simultan dipengaruhi oleh variabel penelitian yang tidak terdeteksi pada penelitian ini.Kata kunci : Kinerja Ekspor, Kebijakan Pemerintah, Sistem Logistik, Kualitas Produk